RIM-MAC:a receiver initiated multi-session MAC protocol for underwater acoustic networks - Chao LI; Yong-jun XU; Bo-yu DIAO; Feng WANG; Qi WANG (Tongxin xuebao)
Acoustic waves are major means of communication in underwater networks.Unfortunately,acoustic waves incur long propagation delays and limited bandwidth that must be taken into account in the MAC design to achieve a high throughput.A multi-session random access MAC protocol for underwater acoustic networks based on receiver reservation named RIM-MAC is proposed.It is a handshaking based protocol that addresses the channel’s long propagation delay characteristic by utilizing receiver-initiated reservations reducing the number of handshaking processes,as well as by passively-acquired local information (i.e.,neighboring nodes’ propagation delay maps and expected transmission schedules) to launch multiple simultaneous sessions.RIM-MAC increases the chances of concurrent transmissions in the underwater channel and achieve the channel reuse at both the sender and receiver side,improving the overall throughput at least 36% compared to the typical MAC protocols.Moreover,a traffic prediction based adaptive data polling scheme named fair traffic algorithm (FTA) guarantees fairness across multiple contending nodes.Extensive simulation results have confirmed that the RIM-MAC protocol outperforms existing MAC protocols and provides fair medium access in representative long propagation delay scenarios.